Effect of Various Preparation Designs on Pull-Out Bond Strength of Endocrown - Naveen Thangarasu; K. Vijay Venkatesh (Indian Journal of Dental Research)
Background: The endocrown is described as monobloc ceramic component. The pull-out bond strength acts as a real-life scenario of failure that occurs in endocrown. The different preparation designs have been included to assess the type of preparation that resists the least failure. Aim: To evaluate the effect of three different types of preparation designs on the pull-out bond strength (PBS) of computer-aided design/computer-aided manufacturing (CAD/CAM) monolithic endocrowns. Methods and Materials: Thirty extracted mandibular first molars were used for this study. Root canal treatment was done. Samples were divided into three groups of 10 samples each. Group A consists of traditional endocrown preparation with a butt joint preparation. The group B consists of a modified preparation with 50-60 degree inward slope. The group C consists of preparation with a 50-60 degree outward slope. Endocrowns were fabricated using CAD/CAM lithium disilicate glass-ceramics. The endocrowns were adhesively bonded to the respective preparations. Pull-out bond strength was calculated using the universal testing machine at a crosshead speed of 1 mm/min. Statistical Analysis: The results were statistically evaluated by one-way ANOVA and Tukey’s post hoc analysis. Results: Group B had higher pull-out bond strength compared to the other two types of preparation designs and showed a statistically significant value with a mean significant difference at 0.05 level (P < 0.05). Conclusion: The 50-60 degree inward bevel in endocrown preparation increased the pull-out bond strength in lithium disilicate endocrowns.